HUBUNGAN ANTARA VITAMIN A DAN PENCAHAYAAN TERHADAP TERJADINYA ASTIGMAT - Susanti, Devi (JURNAL KESEHATAN TERAPAN, 2021)
Background :Astigmat optically is a refractive condition in which a point object is generated as a baying point by an optical system. While astigmat according to the conditions and the literal is within the optical system is not "dot-shaped". Factors related to the occurrence of patients Astigmat is, Descendants, Lighting, Pattern Food Vitamins A, Generation / Age, Visibility, Work, And Ultraviolet On Sun. Objective:Due to cost and time constraints. The authors simply take Vitamin A and lighting on the incidence Astigmat. Methode:This research method using analytic survey with cross sectional approach with a population of 37 respondents, the number of samples taken from the total population. Results of univariate, bivariate and staitsik chi-square test showed no significant correlation between vitamin A with the astigmat with p value 0.000 <0.05, there is a significant relationship between exposure to the astigmat with p value 0,000 <0,05. Suggestion:It is suggested to the leadership determine the policy to develop health services, especially to astigmat as well as in providing a detailed explanation. Keywords: Occurrence Astigmat,Vitamin A, lighting